2022
DOI: 10.1136/jmedgenet-2021-108249
|View full text |Cite
|
Sign up to set email alerts
|

BiallelicCFAP61variants cause male infertility in humans and mice with severe oligoasthenoteratozoospermia

Abstract: BackgroundThe genetic causes for most male infertility due to severe oligoasthenoteratozoospermia (OAT) remain unclear.ObjectiveTo identify the genetic cause of male infertility characterised by OAT.MethodsVariant screening was performed by whole-exome sequencing from 325 infertile patients with OAT and 392 fertile individuals. In silico and in vitro analyses were performed to evaluate the impacts of candidate disease-causing variants. A knockout mouse model was generated to confirm the candidate disease-causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…As the deletion of axonemal proteins frequently disrupts the structural integrity of the axoneme ( 6 , 11 , 26 ), TEM was next used to assess the ultrastructural characteristics of the flagella ( Figure 3 ). Midpiece sections from both a normal control donor and the two KIF9- deficient probands showed mitochondria forming an outer layer with a central axoneme surrounded by ODFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the deletion of axonemal proteins frequently disrupts the structural integrity of the axoneme ( 6 , 11 , 26 ), TEM was next used to assess the ultrastructural characteristics of the flagella ( Figure 3 ). Midpiece sections from both a normal control donor and the two KIF9- deficient probands showed mitochondria forming an outer layer with a central axoneme surrounded by ODFs.…”
Section: Resultsmentioning
confidence: 99%
“…Sperm flagella consist of an evolutionarily conserved axoneme core, composed of nine outer microtubule doublets (DMTs) and a central pair (CP) of microtubules in a 9 + 2 structure. The flagella also include periaxonemal structures, including the mitochondrial sheath (MS) and fibrous sheath (FS) in the midpiece and principal piece regions, respectively, as well as outer dense fibers (ODFs) present in both the midpiece and proximal principal piece regions (6). To date, many singlegene variants have been shown to cause AZS and associated morphological defects by damaging the integrity of these flagellar structures (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…RS1 is adjacent to the base of the inner dynein arm, while RS2 and RS3are respectively attached to the front and back of the nexin–dynein regulatory complex (N-DRC) and the calmodulin- and spoke-associated complex (CSC) ( Zhu et al, 2017 ). Defects of several genes that encode CSC components have been reported to be related to MMAF, including CFAP61 ( Ma A. et al, 2021 ; Liu M. et al, 2021 ; Hu et al, 2022 ), CFAP91 ( Martinez et al, 2020 ), CFAP206 ( Shen et al, 2021 ) and CFAP251 ( Auguste et al, 2018 ; Kherraf et al, 2018 ; Li W. et al, 2019 ; Wang J. et al, 2021 ). Early in 2007, Dymek and Smith conducted immunoprecipitation experiments using anti-CaM antibodies and found that the CSC is comprised of three polypeptides, namely, CaM-IP2, CaM-IP3 and CaM-IP4, which are also termed as CFAP61, CFAP91 and CFAP251, respectively ( Dymek and Smith, 2007 ).…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%
“…Mutations in genes encoding CSC components also affect proper cilia/flagella functioning in vertebrates. In humans, mutations in genes encoding CFAP61 [ 22 , 23 , 24 ], CFAP91/AAT1/MAATS1/C3orf15 [ 19 ], or CFAP251/WDR66 [ 20 , 25 , 26 , 27 ] cause male infertility. This agrees with the gene expression studies in mice [ 23 ] and human tissues [ 28 , 29 ], showing that CFAP61 , CFAP91 , and CFAP251 are highly expressed in testis.…”
Section: Introductionmentioning
confidence: 99%